2013
DOI: 10.4236/aasoci.2013.32017
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment as a Risk Factor for Mental Illness: Combining Social and Psychiatric Literature

Abstract: Unemployment has been shown to have wide ranging effects on physical and mental health. This review looks to clarify the relationship between unemployment and mental illness specifically, in terms of establishing causality, effect size and moderating factors. The current rational for research combines an etiological approach and interest in the social causation of disease with past work from a social psychological perspective. For this review, PsychInfo, Medline and Embase databases were searched between the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
2
14
0
2
Order By: Relevance
“…In line with previous studies, our results demonstrated that unemployment increases the chance of anxiety and depression [20,29,30]. Economically, unemployment status increases the risk of development and progression of psychiatric disorders and strong evidence is available in this regard for depression and anxiety disorders [31][32][33]. Unemployed people may develop some degree of anxiety and depression due to income inequality and the feeling of uselessness, failure, and incompetence [34], especially in countries with weak social security support and unemployment insurance like Iran.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, our results demonstrated that unemployment increases the chance of anxiety and depression [20,29,30]. Economically, unemployment status increases the risk of development and progression of psychiatric disorders and strong evidence is available in this regard for depression and anxiety disorders [31][32][33]. Unemployed people may develop some degree of anxiety and depression due to income inequality and the feeling of uselessness, failure, and incompetence [34], especially in countries with weak social security support and unemployment insurance like Iran.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, our results demonstrated that unemployment increases the chance of anxiety and depression [19,28,29]. Economically, unemployment status increases the risk of development and progression of psychiatric disorders and strong evidence is available in this regard for depression and anxiety disorders [30][31][32]. Unemployed people may develop some degree of anxiety and depression due to income inequality and the feeling of uselessness, failure, and incompetence [33].…”
Section: Discussionsupporting
confidence: 91%
“…Ten (90.9%) of the patients are unemployed. Zhang and Bhavsar (2013) stated that someone who is unemployed has an increased risk of developing mental disorders. Poverty is related to insecurity, lack of education level, inadequate housing, and malnutrition, which can affect the emergence of mental disorders (Kuruvilla & Jacob, 2007).…”
Section: Discussionmentioning
confidence: 99%